2021
DOI: 10.1016/j.scs.2021.102892
|View full text |Cite
|
Sign up to set email alerts
|

What determines city’s resilience against epidemic outbreak: evidence from China’s COVID-19 experience

Abstract: By employing the city-level data from China during the spring of 2020, this study investigates the relationship between city-level resilience against the outbreak of COVID-19 pandemics and its affecting factors, including the inflow risk pressure of COVID-19 virus (population inflow from the epicenter), city agglomeration characteristics (urban population density and city size), healthcare resource adequacy, among others. The results reveal that, while managing COVID-19 inflow risk pressure plays a critical ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 71 publications
1
54
0
4
Order By: Relevance
“…It is clear that public mobility and meteorological factors are highly correlated with the pandemic in many regions worldwide [ 1 , 2 , 3 , 4 , 5 ]. Based on a recent study on data from China, high-density cities (with potentially more mobility factors) were found to be at a higher risk of SARS-CoV-2 infection [ 6 ]. However, how these factors determine the spread of the pandemic remains controversial and under discussion.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that public mobility and meteorological factors are highly correlated with the pandemic in many regions worldwide [ 1 , 2 , 3 , 4 , 5 ]. Based on a recent study on data from China, high-density cities (with potentially more mobility factors) were found to be at a higher risk of SARS-CoV-2 infection [ 6 ]. However, how these factors determine the spread of the pandemic remains controversial and under discussion.…”
Section: Introductionmentioning
confidence: 99%
“…The environment should be designed to prevent the spread of the virus and improve the protection of the residents in buildings and cities [ 3 ]. Large and high-density cities with high inter and intra-city mobility flows have more difficulties in containing the epidemic spread, but improving healthcare infrastructure adequacy and urban governance capacity can increase time efficacy of pandemic control [ 4 ]. Furthermore, improving the governance capacity and infrastructure in regards to residential community is the most effective way to control the epidemic, so as to improve the resilience of cities and communities against pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found to be greater in big and high-density municipalities compared to smaller cities and rural areas [15,16]. Large cities with high inter-and intra-city mobility flows have more difficulties in containing epidemic spread [16]. In many studies, the mobility of the population has been indicated as a key mechanism of the accelerated infectious disease transmission [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The epidemic intensity of COVID-19 is strongly shaped by crowding. It has been found to be greater in big and high-density municipalities compared to smaller cities and rural areas [ 15 , 16 ]. Large cities with high inter- and intra-city mobility flows have more difficulties in containing epidemic spread [ 16 ].…”
Section: Introductionmentioning
confidence: 99%